Resiliencia y proyecto de vida en estudiantes de VII ciclo de la Institución Educativa N° 6010148 Balbina Dora Soto Correa, Caballococha 2025 - Yanse Correa, Jaquelin Mariel (2026)
The study determined the relationship between resilience and life projects in secondary school students from Caballococha. The research was basic in type, with a non-experimental cross-sectional design and a quantitative approach. A sample of 150 seventh-cycle students was used, applying the Wagnild and Young Resilience Scale and García's Life Project Assessment Scale. The results showed a moderate positive correlation between both variables (r=0,636), as well as with the personal competence dimension (r=0,594) and self-acceptance (r=0,616). It was concluded that resilience is significantly related to students' ability to structure their life projects, confirming the proposed hypotheses.